Respuesta :
[tex]\frac{dz}{dt} + e^{t + z} = 0 \ \Rightarrow\ \frac{dz}{dt} = - e^{t + z} \ \Rightarrow\ \frac{dz}{dt} = - e^{t}e^z \ \Rightarrow\ \\ \\
\frac{dz}{e^z} = -e^{t} dt \ \Rightarrow\ \int e^{-z} dz=\int -e^{t} dt \ \Rightarrow\ \\ \\
-e^{-z} = -e^{t} + C \ \Rightarrow\ e^{-z} = e^{t} - C \ \Rightarrow\ -z = \ln(e^{t} - C)\ \Rightarrow\ \\ \\
z = -\ln(e^{t} - C)
[/tex]
By solving given differential equation, Solution is [tex]z=-ln(e^{t}-C)[/tex]
What is a differential equation?
A differential equation is an equation that contains at least one derivative of an unknown function, either an ordinary derivative or a partial derivative.
Given differential equation
[tex]\frac{dz}{dt}+e^{t+z} = 0[/tex]
⇒ [tex]\frac{dz}{dt} = -e^{t+z}[/tex]
⇒ [tex]\frac{dz}{dt}=-e^{t}e^{z}[/tex]
⇒ [tex]\frac{dz}{e^{z} }= -e^{t} dt[/tex]
Apply integration on both sides
⇒ ∫[tex]e^{-z} dz=[/tex] ∫ [tex]-e^{-t} dt[/tex]
⇒ [tex]-e^{-z}=- e^{t} +C[/tex]
⇒ [tex]e^{-z}=e^{t} -C[/tex]
⇒ [tex]-z = ln(e^{t} -C)[/tex]
⇒ [tex]z=-ln(e^{t}-C)[/tex]
By solving given differential equation, Solution is [tex]z=-ln(e^{t}-C)[/tex]
Find out more information about differential equation here
https://brainly.com/question/16663279
#SPJ3